DETERMINANTS OF SUSTAINABLE FINANCE IN BANKING INDUSTRY - Humaira Uswatun Hasanah; Sistya Rachmawati; Etty Murwaningsari (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
This study aims to determine whether the board of directors, independent commissioners, and deposit mobilization affect sustainable finance in banks listed on the Indonesia Stock Exchange in the 2016-2020 period. The population used in this study is banking listed on the Indonesia Stock Exchange in the 2016-2020 period. A total of 45 companies were selected using the purposive sampling method and 183 selected observations with sequential data. The analysis in this study is multiple linear regression. The results of hypothesis testing in this study indicate that the board of directors has a positive effect on sustainable finance. Meanwhile, independent commissioners and deposit mobilization have a negative effect on sustainable finance. The company age, size, and stock market index as control variables in this study affect sustainable finance, while profitability has no effect.